Numerical analysis of the meshless element-free Galerkin method for hyperbolic initial-boundary value problems - Tang, Yaozong; Li, Xiaolin (Applications of mathematics (Prague), 2017)
The meshless element-free Galerkin method is developed for numerical analysis of hyperbolic initial-boundary value problems. In this method, only scattered nodes are required in the domain. Computational formulae of the method are analyzed in detail. Error estimates and convergence are also derived theoretically and verified numerically. Numerical examples validate the performance and efficiency of the method.